New product development and co-creation: A service-dominant logic approach - Dias, Á.; Pereira, L.; Lopes da Costa, R.; Gonçalves, R. (International Journal of Entrepreneurial Venturing, 2022)
Nowadays, we face competitive environments characterised by the proliferation of new technologies, accelerated obsolescence of products and constant change in consumer needs. Companies and organisations need to keep up with changes in the development of new products and services. Interaction with the consumer through co-creation in the new product development process emerges as a process to obtain a competitive advantage and create value for the consumer. Value creation is not inherent to new product development and co-creation. Motivational, emotional, and situational factors alter the success of value creation and can even destroy it. A survey was conducted to measure the variables and test the hypothesis. Results from multiple regression indicate a positive relation between co-creation, innovation, motivation, emotion, value creation, and information and new product development.